Decolonizing Global Health Research: Perspectives from US and International Global Health Trainees. Issue 1 (6th February 2023) - DeCamp, Matthew; Matandika, Limbanazo; Chinula, Lameck; Cañari-Casaño, Jorge L.; Davis, C. Hunter; Anderson, Emily; McClellan, Marlena; Chi, Benjamin H.; Paz-Soldan, Valerie A.
Background: "Decolonizing global health" (DGH) may help global health trainees understand and remediate the effects of historical colonialism on global health, but little is known regarding how trainees perceive DGH. Understanding their perspectives is critical for designing educational interventions tailored to their needs. Objectives: To understand how trainees perceive DGH research and to determine if perspectives differ between trainees from high- (HICs) versus low- and middle-income countries (LMICs). Methods: An online survey of all 2017–2022 pre-doctoral and post-doctoral trainees (n = 111) and mentors (n = 91) within a multi-university program that supports US and international investigators in one-year mentored global health research. The survey evaluated individuals' self-reported knowledge and attitudes toward DGH and their perceptions of historical colonialism's impact on eight aspects of global health. Findings: The response rate to trainee surveys was 56%. Trainees from LMICs were less aware of the concept of DGH; 5/25 (20%) had never heard of DGH and 16/25 (64%) reported that they "know a little, " whereas all HIC trainees had heard of DGH and 29/36 (81%) reported that they "know a little" (p = 0.019). For three aspects of global health (i.e., which research questions get asked; development of collaborative relationships; and data/statistical analyses), trainees from LMICs were more likely to report positive effects of colonialism. However, in open-ended responses, no thematic differences existed between how LMIC and HIC trainees defined DGH (i.e., actively eliminating power imbalances; prioritizing local needs; promoting local leadership; providing equitable opportunities; and ensuring programs are culturally appropriate). Conclusions: Different perspectives surrounding what DGH means suggest a shared understanding may be needed and is arguably prerequisite to designing educational interventions to help global health trainees recognize, understand, and act in global health. Future research is needed to understand perspectives on decolonization across diverse contexts with attention to constructs such as race, ethnicity, and gender.